Acid ceramidase controls proteasome inhibitor resistance and is a novel therapeutic target for the treatment of relapsed / refractory multiple myeloma - Ryan T. Bishop; Tao Li; Praneeth Sudalagunta; Mostafa Nasr; Karl J. Nyman; Raghunandan R. Alugubelli; Mark Meads; Jeremy Frieling; Niveditha Nerlakanti; Marilena Tauro; Bin Fang; Steven Grant; et al. (Haematologica, 2024)
Multiple myeloma (MM) patients are often refractory to targeted therapies including proteasome inhibitors (PIs). Here, analysis of RNA sequencing data derived from 672 patients with newly diagnosed or relapsed/refractory disease identified the acid ceramidase, ASAH1, as a key regulator of PI resistance. Genetic or pharmacological blockade of ASAH1 remarkably restored PI sensitivity and protected mice from resistant MM progression in vivo. Mechanistically, ASAH1 depletion of ceramide promoted SET inhibition of PP2A phosphatase activity thus facilitating the increased expression and activity of the pro-survival proteins, MCL-1, and BCL-2. We corroborated these findings in human MM datasets, and in ex vivo patient MM cells. These preclinical studies suggest that ASAH1 may be a potential therapeutic target for the treatment of relapsed/refractory MM (RRMM).